2016
DOI: 10.1002/ejic.201600899
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of Sterically Bulky Schiff‐Base Magnesium Complexes and Their Application in the Hydrosilylation of Ketones

Abstract: The sterically bulky Schiff-base ligand 1 (L 1 H) was treated with CH 3 MgI in toluene to give the unexpected homoleptic magnesium complex 2 (L 1 MgL 1 ) in good yield. However, the reaction of sterically more bulky ligand 3 (L 2 H) with CH 3 MgI in diethyl ether yielded the desired heteroleptic magnesium iodide 4 [L 2 MgI(OEt 2 )], which was further reduced with sodium to produce the Mg-Na heterodimetallic complex 5. The crystal [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…All other bond dimensions in the title structure agree well with those in previous literature reports. In NUGWES, NUGWIW and NUGWOC (Xu et al, 2009) and in YADZOV (Ma et al, 2016), the lengths of intramolecular O-HÁ Á ÁN hydrogen bonds are especially short, being within the range 1.81-1.88 A ˚.…”
Section: Database Surveymentioning
confidence: 98%
See 1 more Smart Citation
“…All other bond dimensions in the title structure agree well with those in previous literature reports. In NUGWES, NUGWIW and NUGWOC (Xu et al, 2009) and in YADZOV (Ma et al, 2016), the lengths of intramolecular O-HÁ Á ÁN hydrogen bonds are especially short, being within the range 1.81-1.88 A ˚.…”
Section: Database Surveymentioning
confidence: 98%
“…A search of the Cambridge Structural Database (CSD, version 5.42, update of May 2021; Groom et al, 2016) for the (Z)-2-{[(2,4-dimethylphenyl)imino]methyl}-4-methylphenol unit, revealed ten hits where this fragment adopts the enol-imine tautomeric form. The imine bond length (N1-C7) in the title compound is the same within standard uncertainties as the corresponding bond lengths in the structures of 2-(diphenylmethyl)-6-[(mesitylimino)methyl]-4-methylphenol (DEHQIS; Zhou et al, 2012), (R)-N,N 0 -bis(3,5-di-t-butylsalicylidene)-5,5 0 ,6,6 0 ,7,7 0 ,8,8 0 -octahydro-1,1 0 -binaphthyl-2,2 0diamine (MIFXAA; Jia et al, 2002), acetonitrile-bis{2-(mesitylcarbonoimidoyl)-6-[(mesitylimino)methyl]-4-methyl-phenolato}magnesium acetonitrile solvate (QUDZAS; Ghosh et al, 2015), bis{2,4-di-t-butyl-6-[(mesitylimino)methyl]phen-olato}tetrahydrofuranmagnesium (QUDZIA; Ghosh et al, 2015) and 2,4-di-t-butyl-6-{[(2,4,6-tri-t-butylphenyl)imino]-methyl}phenol (YADZOV; Ma et al, 2016). As for the C1-O1 bond [1.353 (2) A ˚], its length compares well with 1.352 (2) A ˚for YADZOV and 1.359 (5) A ˚for DEHQIS.…”
Section: Database Surveymentioning
confidence: 99%
“…Certainly, the discoveries done by the pioneers such as Harder, Hill, Okuda, and Sadow might be brought forward here. [80][81][82][83][84][85][86][87][88] They are less sustainable, and the installation of special ligands requires a number of steps, during which undesired wastes are generated. In this respect, it should however be noted that such research investigations are extremely interesting and provide a wide range of theoretical answers that may have an impact on practical approaches, especially in order to ensure high selectivity for the synthesis of fine chemicals.…”
Section: Hydrosilylation Of Unsaturated Carbon-heteroatom (O N) Moiementioning
confidence: 99%
“…To this end, numerous fluorescent ligands, whose emission changes signficantly on cation complexation, have been developed and employed for the detection of metal ions in biological and environmental samples [5][6][7][8][9][10]. For example, aromatic 2-hydroxy-substituted Schiff bases (1) [11,13,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and hydroxyphenyl and hydroxynaphthylpyridines (2, Scheme 1) [17,[36][37][38] have been shown to act as colorimet-ric, fluorimetic and electrochemical probes for metal ions, because they form complexes with particular cations with high selectivity, which in turn leads to a significant change of their optical or electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%